Sixième Biennale de Paris. - Lassaigne, Jacques (Paris : Musée d'Art Moderne de la Ville de Paris, 1969)
Aamodt, Rolf ; Aasen, Knut ; Abate, Claudio ; Van den Abbeel, Jan ; Adenis, Yves ; Ado ; Agerbaek, Leif ; Agor, Alex ; Aguilera, Pablo Morente ; Ahmadi, Kambiz ; Alea, Hugo ; Alexanco, José Luis ; Alfonso, Reinaldo ; Althaus, Peter ; Alves, Justino ; Alvess, Manuel ; Alvim, Francisco ; Aquino, Edmundo ; Arx, Peter Von ; Assad, Abrao Anis ; Aubert, Jean-Paul ; Aubier, Pascal ; Auer, Alfred ; Autef, Pierre ; Aviado, Virgilio ; Avoine ; Bacigalupo, Massimo ; Bakulic, Dinko ; Ballagh, Robert ; Ballo, Gabor ; Balvanyos, Huba ; Banerjee, Bimal ; Baranger, Alain-Philippe ; Barbe, André ; Barenboim, Mordecai ; Barona, Fernando Batamero ; Barres, Marie-France ; Barres, Michel ; Baruch, Alain ; Baud, Paul ; Baumann, Horst H. ; Beeri, Tuvia ; Belkhodja, Nejib ; Bellocq, Ludovic ; Bencs, Gabor ; Benedit, Luis Fernando ; Benes, Lubomir ; Beran, Zdenek ; Berdoy, Pierre ; Berdyszak, Jan ; Bergallo, Armando ; Berrehar, Hervé ; Betoulaud, Jean-Yves ; Binnendijk, Maarten ; Bircher-Beck, Lina-Maria ; Birkett, Michael ; Blanc, Claude ; Blanc, Jean-Pierre ; Blanchard, Philippe ; Boezem ; Boigeol, Catherine ; Bollar, Gorki ; Boltanski, Christian ; Bombart, Michel ; Bon, Jacques ; Bonnaud, Patrick ; Bonnot ; Boroudjeni, Bahman ; Boulay, Roger ; Bourreau, Jean-Luc ; Boursier, Jacques ; Boutellis, Jean ; Bouthier, Bernard ; Brackenbury, Mike ; Branchi, Walter ; Brandtner, Hans-Joachim ; Braverman, Charles ; Brener, Roland ; Bresler, Henri ; Breteche, Jean-Pierre ; Breyten ; Brigginshaw, Valerie ; Brown, Viviane ; Brunaud, Claudine ; Brunelli, Bruno ; Brusse, Mark ; Bullier, Marie-Marguerite ; Buri, Samuel ; Burt, Michael ; Buser, Remo ; Busfield, Bill ; Busto, Daniel ; Butel, Maxime ; Caballero, Luis ; Cabrera, Benedicto ; Cabu, Jean ; Calacalas, Georges ; Calcagno, Eduardo Raimundo ; etc.
Frans
boek